CHALLENGES OF TEACHER'S ACTIVITY IN TECHNOLOGICAL CREATION DYNAMICS - Callalli Pimentel, Aldo (2014)
This article discusses the new challenges for the teacher and the pedagogical activity in the globalization context, with a special focus on technological expansion, informatics and digital era. In the first section the global positioning of the knowledge society is analyzed. Then, we focus on the importance of technology products and tools necessary for an adequate and effective teaching-learning process in the classroom. Also, there will be a detailed analysis on the characteristics of current technology creation, with a special focus on the teacher and the students creative performance. Finally, we discuss seven challenges for the teacher of the new century with the intention of enabling an effective impact on the educational process in the dynamics of the global village.